Desenvolvimento e validação de metodologias analíticas para análise da cefepima e do metronidazol em plasma e microdialisado peritoneal de ratos Wistar - Anjos, Michele Vaz dos (My University, 2022)
Cefepime (CEF) and metronidazole (MTZ) are two antimicrobial agents which can be used to treat secondary peritonitis. Different analytical methodologies have been described for the quantification of these analytes in biological matrices, but there are no reports addressing the determination of concentrations free of these antimicrobials in the peritoneal fluid of rats. Therefore, this study aimed to develop and validate two analytical methodologies to measure concentrations free of these substances in the peritoneal fluid of Wistar rats. Regarding CEF, a quantification method has been developed by using the technique of liquid chromatography coupled with electrospray ionization high-resolution mass spectrometry (LC-ESI-QTOF-MS), with a Shimadzu Shim-pack CLC-ODS C18 column (250 mm x 4.6 mm) and a pre-column (5 um C18, 4 mm; Phenomenex). The mobile phase consisted of (A) ultrapure water with a pH of 3.5, and (B) acetonitrile (80:20, v/v). The flow rate was 0.8 mL/min, and the injection volume was 20 uL. Quantification was carried out in the positive mode to monitor ions with m/z of 481.1311 for CEF and with m/z of 171.0283 for IS. Regarding MTZ, quantification has been conducted using high-performance liquid chromatography with ultraviolet detection (HPLC-UV/VIS). Chromatography run was carried out on a C18 column, with a flow rate of 1.6 mL/min at 40ºC, with a mobile phase composed of acetonitrile and an aqueous solution of 50 mM monobasic phosphate buffer, with 0.1% of triethylamine at pH 3.0 (10:90, v/v). Linearity was achieved in both methods with a coefficient of determination > 0.99 for plasma and peritoneal fluid matrices. The results of the analytical performance parameters for the analyzed analytes met the criteria of the Food and Drug Administration's Bioanalytical Method Validation Guidance. The applicability of the methods was demonstrated in a pilot pharmacokinetic study in Wistar rats after intravenous administration (bolus) of 110 mg/kg of CEF and 30 mg/kg of MTZ. To determine the pharmacokinetic parameters, the version 6.4 of the Phoenix software was used. [resumo fornecido pelo autor]
A cefepima (CEF) e o metronidazol (MTZ) são dois antimicrobianos que podem ser usados para o tratamento da peritonite secundária. Diferentes metodologias analíticas estão descritas para a quantificação desses analitos em matrizes biológicas, mas não há relatos para a determinação das concentrações livres desses antimicrobianos no fluido peritoneal de ratos. Assim, este estudo tem o objetivo de desenvolver e validar duas metodologias analíticas para medir as concentrações livres desses fármacos no fluido peritoneal de ratos Wistar. Desse modo, para a CEF, foi desenvolvido um método de quantificação empregando a técnica de cromatografia líquida e de detecção por espectrometria de massas de alta resolução com ionização por eletrospray (LC-ESI-QTOF-MS), onde foi empregada uma coluna C18 Shimadzu Shim-pack CLC-ODS (250 mm × 4,6 mm) e uma pré coluna (C18 4 mm, 5 um; Phenomenex). A fase móvel foi composta por (A) água ultrapura com pH a 3,5 e (B) acetonitrila (80:20, v/v). A taxa de fluxo foi de 0,8 mL/min e o volume de injeção de 20 uL. A quantificação foi realizada no modo positivo para monitorar os íons com m/z 481,1311 para CEF e com m/z 171,0283 para o PI. Para o MTZ, a quantificação foi conduzida empregando-se cromatografia líquida de alta eficiência com detecção ultravioleta (CLAE-UV/VIS). A corrida cromatográfica foi realizada em uma coluna C18, com fluxo de 1,6 mL/min a 40ºC, com fase móvel composta por acetonitrila e solução aquosa de tampão fosfato monobásico 50 mM, com 0,1% de trietilamina a pH 3,0 (10:90, v/v). A linearidade foi atingida em ambos os métodos com coeficiente de determinação > 0,99 para as matrizes plasma e fluido peritoneal. Os resultados dos parâmetros de desempenho analítico para os analitos investigados atenderam ao preconizado pelo guia de validação de métodos bioanalíticos da Food and Drug Administration. A aplicabilidade dos métodos foi demonstrada em estudo farmacocinético piloto em ratos Wistar após a administração intravenosa (bolus) de 110 mg/kg de CEF e de 30 mg/kg de MTZ. Para a determinação dos parâmetros farmacocinéticos foi utilizado o software Phoenix versão 6.4. [resumo fornecido pelo autor]
Keywords: Cefepima; Metronidazol; Agentes anti-infecciosos; Peritonite; Ratos Wistar; Cefepime; Metronidazole; Anti-infective agents; Peritonitis; Wistar rats